(3cJGH GdNjds - (3GdHNTj , eMeO Hf eMeO GdHNTj GdNdhJj GdHcaGdhfj,J (B1098 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi cQe BOe hMedge ai GdHQ hGdHMQ s
(3BNQgG (B:s
(3hCf jNJe CYeGdfG HeG jQVjg YfG Efg CQMe GdQGMejf hGdMeO ddg QH GdYGdejf s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B65 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B288s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs